A Review on Employees’ Voluntary Turnover from the Psychological Perspective - Zhen, Yan (International Journal of Psychosocial Rehabilitation, 2020)
High voluntary turnover rate has become the focus of most employers and scholars in related fields. Although employers have attempted to use a variety of retention strategies to retain qualified and skilful employees, the turnover rate remains high in the vast majority of industries around the world. Past researches were concerned mostly on employees’ external demands such as salaries, fringe benefits, work conditions and less focus has been given on the importance of employees’ internal needs based on the psychological capital. Therefore, there is a need to perform a study on the turnover from this perspective as it is crucial not only to retain the individual but also to ensure their satisfaction is fulfilled by their organizations. This paper provides the review of literatures which specifically addresses the perspectives of individual psychology, and simultaneously explains the relationship between the two psychological factors and the turnover intention with the mediating effect of job satisfaction. The arguments are presented to emphasize the needs to carry out this study.